Hindi is our ground, English is our sky : education, language, and social class in contemporary India - LaDousa, Chaise (Berghahn Books, 2014)
A sea change has occurred in the Indian economy in the last three decades, spurring the desire to learn English. Most scholars and media venues have focused on English exclusively for its ties to processes of globalization and the rise of new employment opportunities. The pursuit of class mobility, however, involves Hindi as much as English in the vast Hindi-Belt of northern India. Schools are institutions on which class mobility depends, and they are divided by Hindi and English in the rubric of "medium," the primary language of pedagogy. This book demonstrates that the school division a